Photographs - Nicholson family (1984)
Nine photographs of members of the Nicholson family mentioned in the Nicholson family papers at MS 7009: Rev. Mark Nicholson, Lucy Nicholson, Mark Nicholson, Mark Nicholson's lost Warnambool portrait, William Alleyne Nicholson, 1816-1853 (Leichhardt's patron), John Nicholson, Elizabeth Harvie Cobham (wife of Mark, Jnr. and grandmother of R.M. Jukes), Elizabeth Nicholson (daughter of Rev. Mark Nicholson and sister of John) and Dr. John Nicholson.
Manuscript reference no. : NLA MS 7010.
Mrs Goodacre holds a collection of portraits of the Nicholson family and allowed the Library to make prints of them.
Keywords: Nicholson family -- Pictorial works